The Architecture of Asymmetric Relations through Bibliometrics Analysis - Sinambela, Stivani Ismawira; Nurmandi, Achmad; Al-Fadhat, Faris; Abdelaziz, Zineb (Journal of Islamic World and Politics, 2025)
This study aims to identify a model of Asymmetric Relations in International Relations studies. The method of this study is content and bibliometric analysis based on published journal articles in the SCOPUS Database in the last two decades, from 2004 to 2024. A total of 107 articles met the inclusion criteria. The data from the search results were then analyzed using scientific visualization and the VOS viewer tool to analyze the network relationships underlying the publication and the publication trend information on Asymmetric Relations. The finding revealed that asymmetric relations in the study of International Relations have sub-themes related to war and conflict in the first ten years, and economic themes are discussed in the following ten years. The transformation is associated with the rise of soft power in the economic sector, particularly through China’s Foreign Direct Investment. The main findings of the study on asymmetric relations are (1) A weak position in terms of military power increases threat perception, as realists predict; (2) Shared identity decreases threat perception, as constructivists predict; (3) Shared identity increases cooperation in economic policy areas. This study concluded that through hard power, asymmetric relations can lead to hegemony. In contrast, through soft power, economic stability among countries can be achieved, as reflected in China’s relations with Asian countries.